Service Quality Dimensions of Electricity Services: Evidence from Electricity Board in Sri Lanka. - Achchuthan, S.; Sivathaasan, N.; Jayasundara, J.M.R.S. (Asian Social Science, 2014)
The paper tries to develop an empirical model of service quality in terms of electricity services that may form a basis for a better understanding of its determinants. Specifically, it's aimed to identify the dimensions of servicequality of electricity services provided by the Ceylon Electricity Board located in Badulla District. The studyemploys exploratory factor analysis (EFA) and the service quality dimensions are identified using it as anindependence technique. Data were collected by a structured questionnaire that consists of two sections as Part Aand B. A total of 300 usable responses (n =300) were obtained through simple random sampling technique. Themodel consists of five dimensions such as tangibility, empathy, responsiveness, reliability, and assurance thathave been detected by exploratory factor analysis. Further, results revealed that dimensions extracted from theanalysis accounted for 62.899 percent of the total variance. While the study limits to the electricity servicesprovided by the public sector organization based in Badulla district, the findings introduce the dimensions ofservice quality for electricity services, which may be a base for other scholars.
Keywords: service quality; exploratory factor analysis; Sri Lanka